The trinitarian foundation of human sexuality as revealed by Christ according to Hans Urs von Balthasar: the revelatory significance of the male Christ and the male ministerial priesthood - Pesarchick, Robert A. (Tesi gregoriana / Serie teologia, 2000)
The present study is an attempt to understand the teaching of the Magisterium reserving priestly ordination to men by an exposition and analysis of the revelatory significance of the incarnation of Christ as male, and the relation of his maleness to priestly ordination according to the theology of von Balthasar.